PENGARUH NAMA MEREK TERHADAP KESADARAN MEREK DAN PREFERENSI MEREK MINUMAN SARI BUAH DALAM KEMASAN - ANGGAR DEWI, CHINTIA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: This study aims to analyze and discuss the differences of brand awareness and brand preference based on brand name.This research is conclusive. The population in this study is consumers who know and consume four of bottled juice brand. Samples to be taken of 100 peoples with quota sampling. Measuring instrument used were questionnaires, the data were analyzed with repeated measures anova.The results showed that there are difference beetweenbrand awareness and brand preference based on brand name. Keywords:brand name, brand awarenessand brand preference.